2012
DOI: 10.1016/j.jds.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the oral health-related quality of life and dental pain in symptomatic irreversible pulpitis and pericoronitis

Abstract: KEYWORDS dental pain; pericoronitis; quality of life; symptomatic irreversible pulpitis; VAS Abstract Background/purpose: The oral health-related quality of life (OHRQoL) reveals important information about a patient's perceptions in clinical practice, and pain is a critical point when evaluating OHRQoL in clinical practice. The aim of the study was to compare pain patterns by means of the Dental Pain-Screening Questionnaire (DePaQ) and an OHRQoL evaluation between symptomatic irreversible pulpitis and pericor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…In another study, the level of pain and quality of life were evaluated before root canal therapy in patients with symptomatic irreversible pulpitis. They concluded that higher level of pain had a greater impact on the quality of life [13].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the level of pain and quality of life were evaluated before root canal therapy in patients with symptomatic irreversible pulpitis. They concluded that higher level of pain had a greater impact on the quality of life [13].…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that OHIP-14 is validated for specific conditions e.g. irreversible pulpitis, pericoronitis [5] whilst EQ-5D-5L may have been an option to calculate a score for QoL. We based data collection on the ADHS 2009 framework, specifically theme 3 with OHIP-14 and EQ-5D-5L not validated against the PUFA index.…”
Section: Questionnairementioning
confidence: 99%
“…Oral Health Related Quality of Life (OHRQoL) is a determinant of an individual's wellbeing and relates to oral and dental health [5,6]. In the military, poor OHRQoL has additional consequences for military personnel over their civilian counterparts, reflecting their unique roles and responsibilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptomatic irreversible pulpitis (SIP) is a severe, spontaneous and poorly localised toothache that can be exaggerated by exposure to sudden temperature changes. 1 SIP is a serious degenerative form of pulpal inflammation that may lead to pulpal necrosis and apical periodontitis if left untreated.…”
Section: Introductionmentioning
confidence: 99%